2018
DOI: 10.1080/00221686.2017.1410732
|View full text |Cite
|
Sign up to set email alerts
|

SPHysics simulation of laboratory shallow free surface turbulent flows over a rough bed

Abstract: In this paper, the smoothed particle hydrodynamics method is used to simulate experimental shallow free surface turbulent flows over a rough bed made of regularly packed uniform spheres. The numerical program is based on the open source code SPHysics and significant improvement is made in the turbulence modelling and rough bed treatment within the code. A modified sub-particle-scale eddy viscosity model is proposed to simulate the effect of turbulence transfer mechanisms in the highly-sheared free surface flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…In the original SPS turbulence model, the eddy viscosity coefficient is taken as v t � (C s Δl) 2 |S|, where C s denotes the Smagorinsky constants with a range of 0.1∼0.2 and |S| denotes the local strain rate and can be calculated as |S| � (2S ij S ij ) 1/2 . In this study, the eddy viscosity coefficient is modified with reference to mixed length theory [36] and can be expressed as follows:…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original SPS turbulence model, the eddy viscosity coefficient is taken as v t � (C s Δl) 2 |S|, where C s denotes the Smagorinsky constants with a range of 0.1∼0.2 and |S| denotes the local strain rate and can be calculated as |S| � (2S ij S ij ) 1/2 . In this study, the eddy viscosity coefficient is modified with reference to mixed length theory [36] and can be expressed as follows:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Recently, De Padova et al [35] investigated undular hydraulic jumps over small-scale rough bed for bed roughness of 0.02H, where H denotes the water depth. e SPH mixing-length turbulence model exhibits satisfactory performance for simulating hydraulic jump as long as strong turbulent rollers are not present and is applicable for openchannel flow simulation [25,36]. Overall, there have been insufficient studies of the open-channel flow over rough bed using SPH methods.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the water surface level showed that the SPH results obtained by either way of de¯ning the roughness terrain agreed better with the experimental data than the FV model. More recently, Kazemi et al [2017] and Gabreil et al [2018] treated the bed roughness by including drag force term into the momentum equation to simulate 2D turbulent open channel°ows over¯xed beds. Their results of velocity and shear stress show a good macth with the measured data.…”
Section: Literature Review On Sph Applications In Open Channel Flowsmentioning
confidence: 99%
“…In this case, improvements to the 3D SPH turbulence modeling will be made to address the shear stress, and new treatments of rough beds will be developed to account for the form drag forces due to roughness elements. In this study, the improvements made by Gabreil et al [2018] will be extended by taking into account the in°uence of the 3D°ow near the bed and the side walls of the channel. The improved model will then be used to examine the dynamic behavior of the water surface and its interactions with the underlying°ow structures underneath.…”
Section: Literature Review On Sph Applications In Open Channel Flowsmentioning
confidence: 99%
See 1 more Smart Citation